Physico-chemical properties of Ethiopian Apis mellifera Honey: Review - Sintayehu Berhanu; Dereje Mamo Tadesse; Amauel Jorge (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The aim of this review is focused on the physical, chemical, and antioxidant properties of Ethiopian honey such as moisture contents, reducing sugars (glucose and fructose), free acidity, pH, hydroxymethylfurfural, (HMF), phenolic compounds, minerals, and water-insoluble solid and enzymatic activity of honey. Generally, the average values of the parameter were within the acceptable ranges of National, EU, and FAO/WHO which was set as permission limit requirement for general blossom honey quality. Accordingly, HMF (9.46±7.11mg/kg), moisture contents (18.93%±1.92%), free acidity (23.2±10 meq/kg), pH (3.94±0.14) ash content (0.32%±0.13%), electrical Conductivity (0.41±0.16 mS/cm), water-insoluble solids (0.20%±0.07%), reducing Sugar (70.46%±3.5,0%), and Sucrose (2.75%±1.1%) of the honey was found to be low, this value suggesting that Ethiopian honey were of good quality. The total phenolic contents of honey were high and strongly correlated with the antioxidant activity/radical scavenging capacity. A large portion of research findings are not focused on medicinal value therefore, more research would be important to focus on honey from medicinal plants and to build up the possible relations between the bioactive substances in plant parts and their nectars.